The Novel Map Space and Subjectivity in Nineteenth-Century French Fiction - Bray, Patrick (Northwestern University Press, 2013)
Focusing on Stendhal, Gérard de Nerval, George Sand, Émile Zola, and Marcel Proust, The Novel Map: Mapping the Self in Nineteenth-Century French Fiction explores the ways that these writers represent and negotiate the relationship between the self and the world as a function of space in a novel turned map.With the rise of the novel and of autobiography, the literary and cultural contexts of nineteenth-century France reconfigured both the ways literature could represent subjects and the ways subjects related to space. In the first-person works of these authors, maps situate the narrator within the imaginary space of the novel. Yet the time inherent in the text's narrative unsettles the spatial self drawn by the maps and so creates a novel self, one which is both new and literary. The novel self transcends the rigid confines of a map. In this significant study, Patrick M. Bray charts a new direction in critical theory.